TEACHER’S BELIEFS IN TEACHING READING USING MULTIMODAL TEXT - Rizka Putri Kusuma; Joko Nurkamto; Ngadiso Ngadiso (Universitas Muhammadiyah Semarang, 2021)
Teachers are considered to have an important role in transforming schools and classrooms. They have something to do with successful students learning. It is interesting to note that practically exposed to the same material, curriculum, students and environment, teachers conduct their teaching in various ways because English teachers have preconceived ideas or beliefs about the best approach in their teaching. This reflects the effectiveness of their practice. As multimodal text is necessary to be used in this digital era since text can appear in various forms and do not have to always be in writing consisting of rows of letters or characters. Teachers must have sufficient knowledge and understanding about it. Moreover, before the Covid-19 outbreak appeared in this world and affected all areas, especially education, teaching and learning process in the classroom was still focusing on the use of English textbooks that do not involve various kinds of mode. Therefore, the use of multimodal text is helpful to be used during the pandemic where the teaching and learning process has shifted to online learning. This case study aims to reveal a Senior High School English teacher’s belief about multimodal text in teaching reading. It also reveals how the teacher apply her beliefs in teaching practices. The findings suggest teacher’s personal beliefs about multimodal text and how the use of multimodal text which should be used in the classrooms.